Quantitative effects on cardiovascular risk factors and coronary heart disease risk of replacing partially hydrogenated vegetable oils with other fats and oils. - Mozaffarian, D; Clarke, R (2009)
BACKGROUND/OBJECTIVES: Reduced consumption of trans-fatty acids (TFA) is desirable to lower coronary heart disease (CHD) risk. In practice, partially hydrogenated vegetable oils (PHVO) that contain both TFAs and other fatty acids are the unit of replacement and could be replaced with diverse alternative fats and oils. We performed quantitative estimates of CHD effects if a person's PHVO consumption were to be replaced with alternative fats and oils based on (1) randomized dietary trials and (2) prospective observational studies. SUBJECTS/METHODS: We performed meta-analyses of (1) the effects of TFAs on blood lipids and lipoproteins in controlled dietary trials and (2) associations of habitual TFA consumption with CHD outcomes in prospective cohort studies. On the basis of these results and corresponding findings for saturated fatty acids (SFA), cis-monounsaturated fatty acids (MUFA) and cis-polyunsaturated fatty acids (PUFA), we calculated the effects on CHD risk for replacing 7.5% of energy from three different PHVO formulations (containing 20, 35 or 45% TFAs) with butter, lard, palm or vegetable oils. RESULTS: In controlled trials, each 1% energy replacement of TFAs with SFAs, MUFAs or PUFAs, respectively, decreased the total cholesterol (TC)/high-density lipoprotein cholesterol (HDL-C) ratio by 0.31, 0.54 and 0.67; the apolipoprotein (Apo)-B/ApoAI ratio by 0.007, 0.010 and 0.011; and lipoprotein (Lp)(a) by 3.76, 1.39 and 1.11 mg/l (P<0.05 for each). We also included possible effects on C-reactive protein (CRP) of TFAs vs other fats from one trial. On the basis of these risk factor changes in controlled trials, CHD risk would be variably decreased by different fats and oils replacing 7.5% of energy from 20% TFA PHVO (CHD risk reduction: -2.7% (butter) to -9.9% (canola)); 35% TFA PHVO (-11.9% (butter) to -16.0% (canola)); or 45% TFA PHVO (-17.6% (butter) to -19.8% (canola)). In prospective cohort studies, each 2% energy replacement of TFAs with SFAs, MUFAs or PUFAs would lower CHD risk by 17% (95% confidence interval (CI)=7-25%), 21% (95% CI=12-30%) or 24% (95% CI=15-33%), respectively. On the basis of these associations in observational studies, CHD risk would be variably decreased by different fats and oils replacing 7.5% of energy from 20% TFA PHVO (CHD risk reduction: +0.5% (butter) to -21.8% (soybean)); 35% TFA PHVO (-14.4% (butter) to -33.4% (soybean)); or 45% TFA PHVO (-22.4% (butter) to -39.6% (soybean)). The demonstrated effects on TC/HDL-C, ApoB/ApoAI, Lp(a), and CRP in randomized feeding trials together accounted for approximately 65-80% and approximately 50% of the estimated risk reduction for replacing PHVO with animal fats and vegetable oils, respectively, that would be calculated from prospective cohort studies. CONCLUSIONS: Effects on CHD risk of removing PHVO from a person's diet vary depending on the TFA content of the PHVO and the fatty acid composition of the replacement fat or oil, with direct implications for reformulation of individual food products. Accounting for the summed effects of TFAs on multiple CHD risk factors provides more accurate estimates of potential risk reduction than considering each risk factor in isolation, and approaches the estimated risk reduction derived from prospective cohort studies.